2008
DOI: 10.1080/13668250802478633
|View full text |Cite
|
Sign up to set email alerts
|

People with developmental disabilities teaching medical students – Does it make a difference?

Abstract: Even a brief information session, combined with the opportunity to interact with people with disabilities, can have an impact on medical students' attitudes. Further research is needed to determine how such experiences may influence their future practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 7 publications
5
66
2
2
Order By: Relevance
“…Studies that used measures of attitudes towards persons with disabilities in general also suggested that ID teaching/training enhanced medical students' attitudes (e.g., Tracy & Graves, 1996;Tracy & Iacono, 2008). However, such measurement is problematic as scales non-specific to ID may omit critical aspects of students' attitudes towards this clinical group.…”
Section: Research Suggesting Improved Attitudes: Generic Measuresmentioning
confidence: 93%
“…Studies that used measures of attitudes towards persons with disabilities in general also suggested that ID teaching/training enhanced medical students' attitudes (e.g., Tracy & Graves, 1996;Tracy & Iacono, 2008). However, such measurement is problematic as scales non-specific to ID may omit critical aspects of students' attitudes towards this clinical group.…”
Section: Research Suggesting Improved Attitudes: Generic Measuresmentioning
confidence: 93%
“…For example, Monash University medical students engaged with tutors with intellectual disabilities on a three-hour communication workshop, which increased their understanding and comfort levels with this traditionally underserved community (Tracy & Iacono 2008). At Leeds University, a series of seminars for medical students on 'valuing diversity' were taught, inter alia, by deaf people, disabled people from the local Centre for Integrated Living, people with mental health conditions and people with intellectual disabilities (Thistlethwaite & Ewart 2003).…”
Section: Different Approachesmentioning
confidence: 99%
“…Antes contemplando apenas um tipo de deficiência -como, por exemplo, anamnese de pessoas com deficiência intelectual nas aulas de Psiquiatria -, passam a ser construídas atividades que consideram vários tipos de deficiência 18 . No lugar de atividades isoladas e de curta duração, a partir de 2009 passam a ser distribuídas ao longo do curso médico 19,37,38,39 .…”
Section: Introductionunclassified